How (German) foundations shape the concept of education: Towards an understanding of their use of discourses. Issue 2 (4th March 2017) - Kolleck, Nina
ABSTRACT: In this article I examine how foundations use the concept of education and how they try to shape its definition and implementation. In accordance with Steven Lukes' notion, I argue that changes in social fields are mainly triggered by normative and semantic shifts. By drawing on techniques of discourse analysis, I explore the use of discursive strategies and the discursive interpretations of education, as both its definition and its operationalization have consequences on the identification of educational needs and outcomes. It is shown that foundations regard the use of education as an opportunity to influence values, traditions, and future generations. Furthermore, foundations take part in debates on education in order to increase social influence, to be accepted as legitimate actors in education, and to be perceived as competent and indispensable players in defining educational goals.